Cell-specific α and β subunit expression patterns of Na+/K+-ATPases in the common marmoset cochlea - Makoto Hosoya; Masafumi Ueno; Marie N. Shimanuki; Takanori Nishiyama; Naoki Oishi; Hiroyuki Ozawa (Scientific Reports)
Abstract High potassium concentration in the cochlear endolymph electrically drives hair cell activity. Sodium potassium ATPase (Na+/K+-ATPase) is an essential pump for ion homeostasis in the cochlea. Most of our knowledge regarding Na+/K+-ATPase has been obtained from rodent models, and knowledge of its distribution in primates, including humans, is limited. This study investigated the distribution of Na+/K+-ATPase in a common marmoset primate model. We investigated expression patterns of Na+/K+-ATPase α1 (ATP1A1), Na+/K+-ATPase α2 (ATP1A2), Na+/K+-ATPase α3 (ATP1A3), Na+/K+-ATPase β1 (ATP1B1), Na+/K+-ATPase β2 (ATP1B2), and Na+/K+-ATPase β3 (ATP1B3) in the cochlea of the neonates and the embryos of the common marmoset. We have described the distributions of specific pairs of Na+/K+-ATPase α and β subunits in each cochlear part, including spiral ganglion neurons, stria vascularis, and the organ of Corti. We also described developmental changes in Na+/K+-ATPases in common marmosets. The distribution of Na+/K+-ATPases in the common marmoset is similar to that in humans and is suitable for furthering our understanding of human cochlear development. The distribution established in this report will aid the study of primate-specific ion homeostasis in the inner ear.